Mouse makes words : a phonics reader - Heling, Kathryn; Hembrook, Deborah; Joseph, Patrick, 1961- (New York : Random House, 2002)
By dropping the first letter of a variety of words and adding a new letter, Mouse makes several rhyming words.
"An early phonics book."
Keywords: Vocabulary -- Juvenile literature; Readers (Primary); Vocabulary; Phonics readers